Phosphorylation-driven effector switching of Rab7 and Rab12 by the leucine-rich repeat kinase 1 in mast cells - Omar-Kabha, Jana; Omari, Sewar; Gorzalczany, Yaara; Amer-Sarsour, Fatima; Kleeblatt, Elisabeth; Fukuda, Mitsunori; Ashkenazi, Avraham; Sagi-Eisenberg, Ronit (Frontiers in Immunology, 2025)
IntroductionMast cells (MCs) mediate immune, allergic, and neuroinflammatory responses by releasing inflammatory mediators upon activation through the immunoglobulin E (IgE) receptor FcεRI or innate stimuli acting through Mas-related G protein coupled receptors (Mrgprs). We previously showed that Rab12 negatively regulates mediator release by recruiting the Rab-interacting lysosomal protein (RILP)-dynein complex to the secretory granules (SGs). Because Rab12 also interacts with the RILP-like proteins RILP-L1 and RILP-L2, we examined whether phosphorylation controls Rab12 distribution among its RILP family effectors.MethodsPulldown assays were used to compare the effects of MC activation on Rab12 interactions with its effectors.ResultsHere we show that activation by either IgE/antigen or the neuropeptide substance P, which binds to MRGPRX2, induces phosphorylation of the Rab GTPases Rab7 and Rab12. Phosphorylation of both GTPases was sensitive to protein kinase C (PKC) inhibition but resistant to inhibition of the leucine-rich repeat kinase 2 (LRRK2), a known Rab12 phosphorylating kinase. Furthermore, knockdown of the Leucine-Rich Repeat kinase 1 (LRRK1) suppressed phosphorylation of both Rab7 and Rab12, implicating LRRK1 in their phosphorylation by a PKC-dependent mechanism. Like phosphorylation by LRRK2, LRRK1-mediated phosphorylation of Rab12 increased its affinity for RILP-L1 and RILP-L2 while reducing binding to RILP. In contrast, LRRK1 phosphorylation of Rab7 enhanced its affinity for RILP.